IMPACT OF SOCIALMEDIA ON CUSTOMER RELATIONSHIP MANAGEMENT PERTAINING TO COVID-19 (International Journal of Food and Nutritional Sciences, 2022)
The fact that customer relationship marketing has mushroomed out to benefit and give a competitive edge to the companies practicing it. CRM has moved its branches pertaining to just customers being just traditional marketing to other aspects of business and helping attract goodwill to the company by bringing human touch to the users of the product.CRM has traditionally just associated itself with companies managing relationship with customers. The rise of social media playing a role in almost every aspect of live has connected and empowered the customers to look and expect beyond and covid 19 has surely paved its way in showcasing how important this branch of marketing is.Majority of the data in this report are obtained from secondary source of information mostly from their official website.The unification of social media and CRM has created drawbacks and opportunities which are dealt with in this report discussed and analyzed upon how social media engagement affects the core areas of CRM and supporting business areas before and after covid 19.